Coordination–Entropy Regulation: Toward Unified Design of Hydrogel Electrolytes for Practical Wide-Temperature Zinc-Ion Batteries - Wang, Cong; Zhang, Hong; Wang, Peng; Lu, Ke; Yang, Chun Cheng; Jiang, Qing (Nano-Micro Letters, 2026)
Hydrogel electrolytes have emerged as promising alternatives to conventional aqueous electrolytes in zinc-ion batteries owing to their high ionic conductivity and mechanical robustness. However, hydrogel electrolytes still suffer from stability challenges under wide-temperature conditions. At low temperatures, the freezing of water and the ordering of hydrogen-bond networks restrict ion transport and strengthen the hydrated structure of Zn2+. At high temperatures, water evaporation and intensified parasitic reactions can destroy the electrode–electrolyte interface and induce structural degradation. These coupled thermodynamic and kinetic effects indicate that achieving stable wide-temperature operation requires coordinated regulation of ion transport, solvation thermodynamics and interfacial dynamics. To address this challenge, the coordination–entropy (C-E) regulation framework is proposed as a unified design concept. Within this framework, coordination regulation reconstructs Zn2+ solvation environments and lowers desolvation barriers, while entropy regulation increases the diversity of accessible ionic configurations and transport states across multiple structural scales. Their intrinsic coupling enables stable ion transport and interfacial chemistry under temperature variation. This review systematically summarizes recent advances in polymer, salt, cosolvent and filler regulation strategies directed by the C-E framework, aiming to establish a unified physicochemical framework for wide-temperature hydrogel electrolytes and guide the development of durable, high-energy–density zinc-ion batteries. Highlights: 1 Critical limitations of hydrogel electrolytes operation under wide-temperature conditions are systematically summarized. 2 A coordination–entropy regulation framework is proposed to unify Zn2+ solvation chemistry, electrolyte thermodynamics and interfacial kinetics. 3 Future directions for practical wide-temperature zinc batteries are comprehensively discussed.